BETWEEN LEGAL RISK AND SHARIA RISK IN ISLAMIC BANKING: HOW SHARIAH GOVERNANCE ADDRESS THE PROBLEM - Iffah Karimah (Fakultas Hukum, Universitas Diponegoro, 2022)
Islamic Bank has unique risk due to its Sharia-compliance principles. Two of risksknown in Islamic Banking are legal risk and sharia risk. This paper aims to explain the legal risk and sharia risk faced by Islamic Banking in Indonesia. Moreover, this paper also will discuss the cause of these risks and its mitigation strategy using Shariah Governance concept. This paper using literature studies from previous research and existing regulation in Indonesia. This research shows that Islamic Banking in Indonesia has unique legal risks and sharia risk due to its adherence to a dual law system: shariah law and national law. There are several causes of legal risk and sharia risk in Islamic Banking in Indonesia, such as lack of supporting legal system and regulation, lack of standardization contract in Islamic Banking, and lack of Court Systems to resolve Islamic Banking’sproblem. Moreover, there are severalissues on the product development process in Islamic Bank. In addition, this paper explores the role of Shariah Governance such as Sharia Supervisory Body and National Shariah Board as a solution to address the problem stemming from legal risk and sharia risk.